A MULTIMODAL ANALYSIS OF TWEETS BY THE ANTI-BUILDING BRIDGES INITITIAVES (BBI) MICRO-BLOGGERS IN KENYA - JOYLENE SOPHIA NGAU (Machakos University Press, 2025)
The purpose of this study was to carry out a multi-modal analysis of the emotive lexicons, syntactic structures, and conceptual metaphors that were used by the anti-BBI (Building Bridges Initiatives) bloggers in Kenya. The study addressed the following objectives: identify the nature of the emotive lexicons used in the construction of anti BBI tweets; establish the conceptual metaphors that were used in the construction of the anti-BBI tweets; and analyze the functional elements of syntactic structures on Twitter. According to the literature on political discourse, Twitter has risen to prominence as the primary communication tool for disseminating political messages and articulating political agenda. The research was based on multi-modal analysis theory and conceptual metaphor theory. The study presented a quantitative description of the multi-modal analysis of the tweets used by the anti-BBI bloggers. The multi modal theoretical framework and the conceptual metaphor theory was employed in the analysis of data from written tweets and visual aspects of the tweets that were used in the anti-BBI tweets. In the study, stratified constructed-week sampling was used, followed by purposive sampling techniques. A checklist was also utilized to determine the data that suits the study. The mixed research approach was applied to analyze how the multi-modal responses shaped the discourses against the Building Bridges Initiative in Kenya. The study findings showed that 79% of the tweets used emotive words to push their agenda in the anti-BBI discourse, 74% of the proponents of the anti-BBI discourse used conceptual metaphors while 54% of the tweeps focused on how syntactic structures were employed in the posting of anti-BBI tweets. Further, the key syntactic structures feature in the selected data entailed the use of ellipsis in sentence structure, substitution, and poor punctuation, use of short form as well as intra and inter sentential emojis. The findings provided critical insights on the emotive lexicon, conceptual metaphors, and syntactic structures and their correlation to Section 5B, Part 4 KICA (2019), which forms a critical pillar in the language use and its place in boosting national integration. The recommendations drawn from the study include a need to strengthen Kenyan communities and social bonds among ethnic groups to reduce feelings of isolation and alienation that can make individuals more susceptible to polarizing discourse on Twitter. This promotes education and critical thinking skills to help individuals recognize and counter emotive discourse when they encounter it, encouraging open dialogue and respectful debate to foster understanding and tolerance among people with different views, a need to hold those who engage in emotive discourse accountable for their actions, and whether through social sanctions or legal consequences. Additionally, need for media literacy programmes that teach people how to identify and evaluate the credibility of information sources as well as helping them discern between legitimate arguments and emotive language. Within the applied linguistic field, institutions such as the Ministry of Education to develop for language planning and policy development shall use the study